The Utilization of 30-Juz Murottal Qur’anic Media in Supporting the Student Memorization Program at SMP Darussalam Tanggul - M. Rofi'ul Haq; Zuhri Fahruddin (IQRO: Journal of Islamic Education, 2026)
This study aims to determine students’ responses to the use of murottal in the process of memorizing the Qur’an, analyze its effectiveness in improving the quality of memorization in terms of fluency, accuracy of tajwid, and memory retention, and provide practical recommendations for developing Qur’an memorization programs in educational settings. The research was conducted at SMP Darussalam Tanggul, involving students as the main respondents. The approach used was adjusted to the characteristics of the participants and the learning needs. Data collection techniques included observation, interviews, and documentation. Initial observation was conducted on December 29, 2025, and continued from January 7 to February 18, 2026, by directly observing the learning process and the implementation of murottal media. Interviews were conducted with the tahfidz teacher, the principal, and students to explore their experiences, challenges, and perceptions regarding the effectiveness of murottal. Documentation included activity schedules, assessment rubrics, photographs, and the murottal media used in the learning process. The results show that the use of murottal received positive responses from students and contributed to improvements in reading fluency, tajwid accuracy, and memory retention through structured audio repetition. The study recommends the systematic integration of murottal media to enhance the effectiveness of Qur’an memorization programs